One cycle start‐up time, high linearity relaxation oscillator with capacitor pre‐charge technique. Issue 21 (1st October 2018) - Lu, Yangyang; Zhu, Jing; Hu, Kongsheng; Yu, Siyuan; Sun, Weifeng; Zhang, Yunwu; Zhang, Long
Abstract : A capacitor pre‐charge technique based CMOS relaxation oscillator is proposed to improve its linearity adaptively. The effect of comparator offset and delay variation across PVT will be counteracted by the pre‐charge process because it is included both in the effective charge process and the pre‐charge process. Then, the non‐linearity of the oscillator caused by the delay of the control circuit and the offset voltage of the comparator can be eliminated. The proposed relaxation oscillator with a typical frequency of 100 kHz is implemented in 0.5 μm Bipolar‐CMOS‐DMOS process. Measured results show that <0.54% non‐linearity in the current–frequency transfer function from 0 to 5 MHz without trimming.